PENGARUH KOMPTENSI LITERASI DIGITAL DAN SELF REGULATED LEARNING TERHADAP MOTIVASI BELAJAR MAHASISWA - Sri Mulyati (Institut Pendidikan Tapanuli Selatan, 2023)
This study aims to describe the effect of digital literacy competence and self-regulated learning on student learning motivation with blended learning patterns. The population in this study were all students of Economics Education level I to IV for the 2022-2023 academic year, a total of 83 students. The type of research used is quantitative research with survey methods. The data collection technique used is through questionnaires. The data analysis technique was performed using multiple regression. The results of the study show that there is a positive and significant influence both partially and simultaneously between digital literacy and self-regulated learning on student learning motivation. Increasing competence and skills in mastering digital literacy and optimizing self-regulated learning for students in chapter 21, which is often referred to as the digitalization era, is urgently needed to continuously increase learning motivation. Efforts to increase learning motivation continuously need to be improved considering the quality of learning is very dependent on how students are motivated to be active and enthusiastic in attending lectures.